Gender Differences in the Suicide Attempts of Adolescents in Emergency Departments: Focusing on Individuals with Autism Spectrum Disorder - Mikami, Katsunaka; Inomata, Seiji; Onishi, Yuichi; Orihashi, Yasushi; Yamamoto, Kenji; Matsumoto, Hideo (Adolescent Psychiatry, 2019)
Background: Few studies on gender-based diagnostic characteristics of adolescent suicide attempters in emergency departments (EDs) have included individuals with autism spectrum disorder (ASD). Objective: This study aimed to examine the clinical features of adolescent suicide attempts in EDs, focusing on gender differences and considering individuals with ASD. Methods: Ninety-four adolescent patients, aged less than 20 years, who had attempted suicide and had been hospitalized in an emergency department, participated in this study. Psychiatric diagnoses according to DSM-IV criteria and clinical features were compared between male and female patients. Results: The number (%) of males was 15 (16.0), and that of females was 79 (84.0). The mean age (SD) of males was 17.1 (1.5), and that of females was 16.9 (1.6). The attempt methods were more serious, length of stay in the emergency room longer, and rate of outpatient treatment lower in males. In addition, suicide attempters with ASD were significantly more frequent in male. Adjusting for age and gender, adjustment disorder was significantly associated with the presence of suicide attempters with ASD using a multivariable logistic regression. Conclusion: Males were less likely to visit psychiatric service previous to attempting suicides, and may be likely to complete suicides. In addition, suicide attempters with ASD are characteristic in male, and likely to have comorbid adjustment disorder. ED visits offer a window of opportunity to provide suicide prevention interventions for adolescents, and therefore, psychiatrists in EDs have a crucial role as gatekeepers of preventing suicide reattempts, especially in adolescent males including individuals with ASD having adjustment disorder.
Keywords: Suicide